Encapsulation of Gemor Bark Extract Using Cetyltrimethylammonium bromide-Modified Nanocellulose - Salsabila Aqila Putri; Sunardi Sunardi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2021)
Gemor (Nothaphoebe coriacea) is one of the plants of Non-Timber Forest Product typical of wetlands with secondary metabolite compounds such as alkaloids, steroids, flavonoids, triterpenoids, and phenolics. Besides being used as an insecticide, gemor bark also has antioxidant activities, anti-influenza, antivirus, antiherpes, and anti-inflammatory. This study aimed to encapsulate gemor bark extract using cetyltrimethylammonium bromide (CTAB)-modified nanocellulose to increase the effectiveness of its use. The result showed that gemor bark extract had an IC50 value of 39.97 ppm. In comparison, encapsulated gemor bark extract (Gemor-Nc-4 mM CTAB) had an excellent antioxidant activity with an IC50 value of 98.41 ppm and encapsulation efficiency of 53.70 %.